Intracranial mesenchymal tumor with FET‐CREB fusion—A unifying diagnosis for the spectrum of intracranial myxoid mesenchymal tumors and angiomatoid fibrous histiocytoma‐like neoplasms. (28th January 2021) - Sloan, Emily A.; Chiang, Jason; Villanueva‐Meyer, Javier E.; Alexandrescu, Sanda; Eschbacher, Jennifer M.; Wang, Wesley; Mafra, Manuela; Ud Din, Nasir; Carr‐Boyd, Emily; Watson, Michael; Punsoni, Michael; Oviedo, Angelica; et al.
Abstract: Intracranial mesenchymal tumors with FET‐CREB fusions are a recently described group of neoplasms in children and young adults characterized by fusion of a FET family gene (usually EWSR1, but rarely FUS ) to a CREB family transcription factor ( ATF1, CREB1, or CREM ), and have been variously termed intracranial angiomatoid fibrous histiocytoma or intracranial myxoid mesenchymal tumor. The clinical outcomes, histologic features, and genomic landscape are not well defined. Here, we studied 20 patients with intracranial mesenchymal tumors proven to harbor FET‐CREB fusion by next‐generation sequencing (NGS). The 16 female and four male patients had a median age of 14 years (range 4–70). Tumors were uniformly extra‐axial or intraventricular and located at the cerebral convexities (n = 7), falx (2), lateral ventricles (4), tentorium (2), cerebellopontine angle (4), and spinal cord (1). NGS demonstrated that eight tumors harbored EWSR1 ‐ ATF1 fusion, seven had EWSR1 ‐ CREB1, four had EWSR1 ‐ CREM, and one had FUS ‐ CREM . Tumors were uniformly well circumscribed and typically contrast enhancing with solid and cystic growth. Tumors with EWSR1 ‐ CREB1 fusions more often featured stellate/spindle cell morphology, mucin‐rich stroma, and hemangioma‐like vasculature compared to tumors with EWSR1 ‐ ATF1 fusions that most often featured sheets of epithelioid cells with mucin‐poor collagenous stroma. These tumors demonstrated polyphenotypic immunoprofiles with frequent positivity for desmin, EMA, CD99, MUC4, and synaptophysin, but absence of SSTR2A, myogenin, and HMB45 expression. There was a propensity for local recurrence with a median progression‐free survival of 12 months and a median overall survival of greater than 60 months, with three patients succumbing to disease (all with EWSR1 ‐ ATF1 fusions). In combination with prior case series, this study provides further insight into intracranial mesenchymal tumors with FET‐CREB fusion, which represent a distinct group of CNS tumors encompassing both intracranial myxoid mesenchymal tumor and angiomatoid fibrous histiocytoma‐like neoplasms. Abstract : Intracranial mesenchymal tumors with FET‐CREB fusion comprise a group of neoplasms that have been variably described as intracranial angiomatoid fibrous histiocytoma and intracranial myxoid mesenchymal tumor. Our investigation reveals that these tumors occur in a wide age range with a female predominance, usually have extra‐axial or intraventricular location, typically have solid and cystic growth pattern with enhancement after contrast administration, and demonstrate a propensity for local recurrence and occasionally dissemination or metastasis leading to mortality. These tumors demonstrate a broad range of histologic features, with those harboring CREB1 or CREM as the fusion partner enriched for stellate/spindle cell morphology and mucin‐rich stroma, versus those with ATF1 as the fusion partner enriched for epithelioid/rhabdoid morphology and mucin‐poor stroma.